2019
DOI: 10.1002/jnm.2697
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of microchannel with different pin fin layouts

Abstract: A numerical analysis is carried out in this study to understand the effect of the different pin fin layouts in the microchannel heat sinks. The performance analysis is done using the conjugate heat transfer module of COMSOL Multiphysics software. Initially, a microchannel with elliptical pin fins of 500-μm fin height in it is validated with the results from the literature. Further, the performance of microchannels with three different pin fin layouts is compared with the baseline model. The investigation is do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The present study desired to examine the possibility of manipulation of neighbouring bubble pairs, and for the neighbouring bubbles in the u-Janus and d-Janus cases to stretch perpendicular to the flow direction during their pairwise merging phase. In this configuration, the greatest drag forces would be experienced by bubbles, while the pressure drop in single-phase regions were expected to be small [6,7].…”
Section: Chip Designmentioning
confidence: 99%
“…The present study desired to examine the possibility of manipulation of neighbouring bubble pairs, and for the neighbouring bubbles in the u-Janus and d-Janus cases to stretch perpendicular to the flow direction during their pairwise merging phase. In this configuration, the greatest drag forces would be experienced by bubbles, while the pressure drop in single-phase regions were expected to be small [6,7].…”
Section: Chip Designmentioning
confidence: 99%
“…It was also identified that the thermal performance surged with rising of coolant velocity and with fin height. They further studied 19 the effect of staggered elliptical fin layout on the thermal characteristic of the channel. The results indicated that the cooling performance of the staggered elliptical fin layout was better than the in‐line arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Jadhav et al. 32,33 compared the performance of microchannel heat sink based on three different layouts and shapes of fins such as ellipse, circle, square and hexagon and revealed that staggered arrangement boosts the heat transfer than inline arrangement. Yu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Saravanan et al 31 compared the characteristics of heat transfer for micro pin fin and microchannel pin fin heat sink with different shapes of pin fins specifically square and circular and finds that due to secondary vortices generated, fins of square shape enhance the heat transfer when contrasted with the circular one. Jadhav et al 32,33 compared the performance of microchannel heat sink based on three different layouts and shapes of fins such as ellipse, circle, square and hexagon and revealed that staggered arrangement boosts the heat transfer than inline arrangement. Yu et al 34 proposed novel Piranha Pin Fin design to boost the heat transfer which is used in both either in a singlephase or in a double phase flow because of its vapour venting property.…”
Section: Introductionmentioning
confidence: 99%